2020
DOI: 10.1177/1129729820927914
|View full text |Cite
|
Sign up to set email alerts
|

Liposuction used to treat deep vascular accesses for hemodialysis

Abstract: Background: Oftentimes, obese dialysis patients develop a viable dialysis access but the access is too deep for cannulation and needs a superficialization procedure. Methods: We present our 14-patient cohort in whom we performed liposuction to superficialize viable but deep vascular accesses. Out of 14 patients, 12 had arteriovenous fistulas and 2 arteriovenous grafts. The primary end points were the ability to superficialize a completely unusable access and to remove the hemodialysis catheter (3patients), or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…A significant benefit of the liposuction technique is less tissue dissection, smaller incisions, lower risk of wound healing complications, and potentially faster recovery. Previous case reports and smaller cohort studies have reported liposuction to be an effective and welltolerated technique with a lower complication profile [8][9]11,[16][17][18] . Our cohort's findings are reflective of this, as AVF cannulation was successful in 79% of patients, with minor complications that were medically managed.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 96%
See 4 more Smart Citations
“…A significant benefit of the liposuction technique is less tissue dissection, smaller incisions, lower risk of wound healing complications, and potentially faster recovery. Previous case reports and smaller cohort studies have reported liposuction to be an effective and welltolerated technique with a lower complication profile [8][9]11,[16][17][18] . Our cohort's findings are reflective of this, as AVF cannulation was successful in 79% of patients, with minor complications that were medically managed.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 96%
“…Traditional superficialization procedures used include AVF transposition, AVF vein elevation and direct lipectomy. These procedures typically necessitate longer skin incisions, dissection of the AVF, ligation of side branches, movement of vein impacting angle and torsion of the vessel [6][7][8][9][10][11][12][13][14][15]21 . Liposuction or combination liposuction-minimally invasive lipectomy with incision less than 2 cm offers an alternative to the traditional approaches.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 3 more Smart Citations